The Skeptic’s Guide to Information Sharing at Sentencing - Scott, Ryan W. (2013)
The “information sharing model,” a leading method of structuring judicial discretion at the sentencing stage of criminal cases, has attracted broad support from scholars and judges. Under this approach, sentencing judges should have access to a robust body of information, including written opinions and statistics, about previous sentences in similar cases. According to proponents, judges armed with that information can conform their sentences to those of their colleagues or identify principled reasons for distinguishing them, reducing inter-judge disparity and promoting rationality in sentencing law. This Article takes a skeptical view of the information sharing model, arguing that it suffers from three fundamental weaknesses as an alternative to other structured sentencing reforms. First, there are information collection challenges. To succeed, the model requires sentencing information that is written, comprehensive, and representative. Due to acute time constraints, however, courts cannot routinely generate that kind of information. Second, there are information dissemination challenges. Sharing sentencing information raises concerns about the privacy of offenders and victims. Also, the volume and complexity of sentencing decisions create practical difficulties in making relevant information accessible to sentencing judges. Third, the model’s voluntariness is an important drawback. The information sharing model rests on the heroic assumption that judges will respond to information about previous sentences by dutifully following the decisions of their colleagues. That is unrealistic. Judges just as easily can disregard the information, ignore it, or even move in the opposite direction. Despite those grounds for skepticism, information sharing can play a valuable role as a supplement to other sentencing reforms. In particular, information sharing would benefit from a system of sentencing guidelines, whether mandatory or advisory, and from open access to the information on the part of defense counsel and prosecutors